2016
DOI: 10.1017/cem.2016.246
|View full text |Cite
|
Sign up to set email alerts
|

P070: Improving handovers in the emergency department: implementation of a standardized team approach

Abstract: to additional training. Our study emphasizes that our physicians have the skill set to identify and provide care for sepsis using their clinical judgment in cases that may not require protocolized based care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…At the study outset, no standard format for physician-to-physician handover between shifts was being used in our ED. Previous resident research within our department confirmed that patients admitted to inpatient care or referred to a consultant service (‘boarded patients’) but not yet seen were frequently omitted from intershift handover communication between ED physicians 7 8. Additionally, informal observations of handovers leading up to this quality improvement (QI) initiative revealed that up to 25% of patients still in active care of the ED team (eg, pending discharge or transportation) were often omitted from handovers between ED physicians, and up to 50% of patients referred to specialty consultants were omitted from these handovers.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…At the study outset, no standard format for physician-to-physician handover between shifts was being used in our ED. Previous resident research within our department confirmed that patients admitted to inpatient care or referred to a consultant service (‘boarded patients’) but not yet seen were frequently omitted from intershift handover communication between ED physicians 7 8. Additionally, informal observations of handovers leading up to this quality improvement (QI) initiative revealed that up to 25% of patients still in active care of the ED team (eg, pending discharge or transportation) were often omitted from handovers between ED physicians, and up to 50% of patients referred to specialty consultants were omitted from these handovers.…”
Section: Introductionmentioning
confidence: 90%
“…We performed a literature review of published articles describing handover practices, that focused on ED-specific models and experiences with demonstrated positive quality and safety improvements 1 3 4 7 8 10 12 14 16–18 20–23 25. There is no gold standard that is currently accepted to define ‘adequate’ ED intershift handover.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation